SAML based context aware IDM a fine-grained proxy re-encryption approach to improve the privacy of users identity data in cloud environment - S Srinivasa Reddy Modugula, T; Vijaya Babu, B; Pachala, Sunitha; Chiramdasu, Rupa; Sumalatha, L (International Journal of Engineering and Technology, 2018)
Cloud computing has made tremendous changes in IT industry by offering various services ranging from Iaas, Saas, Paas, Daas, IDaas to Xaas i.e. everything as a service. Identity as a service is one of the popular service offered by cloud providers which is used for Identity and Access Management which reduces the burden of identity management to companies. As the Identity data of user's moves out of organizational boundaries to cloud servers, the control over identity data is lost thereby security and privacy issues arise. To address these issues many Identity management systems have been proposed but none of them provided privacy at the fine-grained level. In this paper, we propose a SAML based ContextawareIdM, a model for fine-grained privacy-preserving identity as a service which employs Identity-based conditional proxy re-encryption to maintain and operate identity data's privacy at a fine-grained level.